Re-introduction of local government election: Sarawak perspective / Akmal Farid Bujang and Ningkan Aziz - Bujang, Akmal Farid; Aziz, Ningkan (2012)
Local government, also called local authority, is the third level of government. Although the smallest and perhaps least powerful compared to the other two (state and federal), it has an important role to play in a democratic society. We will focus more towards Reintroduction of Local Government Election: Sarawak Perspective. 25 residents and 25 council members of municipalities’ government in Sarawak, which are in Kuching, Sibu, and Miri, will be randomly selected to answer our questionnaire on reintroduction of Local government election. The public awareness regarding the local government election also examined. On the city council side, they will be questioned about reintroduction of local government election. The findings shows that majority of our respondent agree for reintroduction of the third vote.